DEVELOPMENT OF AI AND VR TECHNOLOGY IN ARCHITECTURAL FIRMS - Eliana, Stacey; Fayola, Karen; Marcelino, Bong; Pamudji, Muhamad; Nuradhi, Maureen (Aksen : Journal of Design and Creative Industry, 2024)
In the 4.0 era, many industries combine technology such as the world of design where AI and VR are widely used for reasoning, exploration, visualization, and design innovation. The use of AI and VR in the field of architecture is not something new, previously the theory of AI was discovered in 1956 by Mccarthy and was created to produce intermediate information parameters by imitating the statistical distribution of the information presented as a result of changing options, this concept is the core paradigm from AI and VR theory. Many architecture firms struggle to combine enterprise architecture and technology creation for business strategy. AI and VR can reduce design and development time by as much as 10% and 7%, also minimizes errors that occur in projects by 90%. The research aims to prove that AI and VR help make decisions in the planning and design stages through mixed methods, namely qualitative as a literature study to analyze the use of AI and VR in architecture and quantitative with surveys to analyze interest and feasibility. Based on validated literature, it’s evident that AI and VR advancements are poised to significantly benefit architectural firms by aiding in decision-making, minimizing risks and costs through visualization and calculations, as supported by a survey of 40 architects across 4 bureaus, indicating their crucial role in both current and future architectural practices, with potential to garner substantial market interest, revolutionizing design innovation and efficiency. Keywords: AI, Architecture Firm, Enterprise Business, Digital Entreprenuership, VR.